Cross-country comparison of the replacement incentives of the EU ETS in 2008-12: the case of the power sector - Karoline S. Rogge; Christian Linden (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
In this paper, we conduct a cross-country quantitative analysis of the replacement incentives generated by the EU ETS for the power sector in 2008-12. In order to do so, the allocation rules of the Member States are applied to concrete reference power plants for three different fuel types (lignite, hard coal and gas). Based on these calculations, we compare installation-specific replacement in-centives across the Member States. Our analysis shows that replacement incentives vary significantly across Member States and typically deviate from the incentives provided in the reference case of full auctioning. Furthermore, the EU ETS allocation rules lead to perverse incentives in approximately 30% of the possible replacement options. Only 5 MS do not provide any perverse incentives. Finally, we explore the link between replacement incentives and allocation types. Based on our findings, we derive policy recommendations for the design of emission trading schemes emerging around the world.
urn:nbn:de:0011-n-1193399
Keywords: 330; EU emission trading scheme (EU ETS); replacement; adoption; diffusion; power sector; allocation rules